2022
DOI: 10.1186/s12302-022-00685-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the 2021 summer flood in Central Europe

Abstract: The flood event in July 2021 in the uplands of the Eifel-Ardennes mountains in Germany, Belgium and The Netherlands and their foreland was caused by heavy rainfall and resulted in one of the largest flood disasters in Western Europe for decades. Due to climate change, it can be assumed that such events will become more frequent in future. Even though such extreme flood can happen at any time, the consequences and impacts can be significantly reduced by appropriate technical and non-technical measures. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…During floods, LW poses a hazard for impacts at instream structures [36,85] but also bridge scour and backwater effects in case of LW accumulations [33,57,76,89]. Incidents involving wood in transit and damage due to LW accumulations at critical instream infrastructure are increasingly reported all over the world, and thus require more attention and an improved understanding of intrinsic movement dynamics of LW during floods [20,29,44,91].…”
Section: Large Wood (Lw) In Fluvial Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…During floods, LW poses a hazard for impacts at instream structures [36,85] but also bridge scour and backwater effects in case of LW accumulations [33,57,76,89]. Incidents involving wood in transit and damage due to LW accumulations at critical instream infrastructure are increasingly reported all over the world, and thus require more attention and an improved understanding of intrinsic movement dynamics of LW during floods [20,29,44,91].…”
Section: Large Wood (Lw) In Fluvial Environmentsmentioning
confidence: 99%
“…A total of three rivers in Switzerland were selected for SmartWood experiments in the course of the present study. All experiments were conducted after heavy precipitation events in the summer of 2021, which has led to severe flooding in central Europe [44].…”
Section: Field Sitesmentioning
confidence: 99%
“…Vice versa, the question arose whether recent drought measures may have intensified the summer flood. Furthermore, the floods of 2021 called for an improved and better-aligned transnational approach of river flooding and river management (Lehmkuhl et al, 2022) and more focus on regional small rivers that are not protected by dikes. Additionally, it is important to mention that the Meuse river itself did not flooda success story of the flood policy program 'Room for the River'.…”
Section: VImentioning
confidence: 99%
“…With these droughts on our minds, the contrast to the 2021 summer floods in the Ahr, Erft, Meuse, and its tributaries in Belgium, Germany, and the Netherlands was large. These floods were caused by 2 days of extreme rainfall on hilly terrain and led to more than 200 fatalities and severe infrastructural damage (Kreienkamp et al, 2021;Faranda et al, 2022;Lehmkuhl et al, 2022). This string of very impactful hydrometeorological events, on both sides of the flood-drought spectrum, reminded policymakers and citizens that climate change is a reality and that increases in both droughts and floods require a shift in water management solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Besides coastal communities, many inland areas are also at risk of higher levels of extreme flooding due to climate change, as a result of increased pluvial and fluvial flood risk (IPCC, 2022;Merz et al, 2021). As a case in point, recently, extreme precipitation events caused unprecedented flood disasters in Northwest Europe (2021) and Pakistan (2022) (Lehmkuhl et al, 2022;Nanditha et al, 2023), and research has shown that these events are (partly) attributed to climate change (Otto et al, 2023;Tradowsky et al, 2023).…”
Section: Sea-level Rise and Extreme Flooding Under Climate Changementioning
confidence: 99%